A rare case of rickettsial fever with isolated third cranial nerve palsy causing hemophagocytic lymphohistiocytosis (Indian Journal of Case Reports, 2021)
Rickettsial infections are being increasingly diagnosed in the Indian subcontinent with the advent of affordable and sensitive diagnostic techniques. Rickettsial infections are sometimes complicated by the development of secondary hemophagocytic lymphohistiocytosis (HLH) which is life-threatening unless identified early and treated. Here, we describe a case of rickettsial fever in a 41-year-old male who presented with fever, skin rash, and neurological obtundation, complicated by both third cranial nerve palsy and HLH. The patient showed a good recovery in sensorium with intravenous doxycycline and dexamethasone, although the oculomotor nerve palsy persisted for about two months after discharge. This case highlights the need to initiate treatment for rickettsial fever and HLH on clinical grounds before waiting for confirmation by laboratory tests.